Exploring the Training Mode of Applied Talents Based on OBE. (June 2020) - Li, Bai; Maalla, Allam
Abstract: Since the 18th National Congress of the Communist Party of China, education has been established with the fundamental task of establishing a person. It has promoted the transformation of local undergraduate colleges and private colleges to applied universities. Introduce OBE as a theoretical support for the cultivation of talents in applied universities, establish a life-oriented, competency-based education concept, and build a training system for applied talents. In particular, it will connect with professional groups within the social industry and summarize the corresponding professional capabilities. Construct a practical teaching system from the mode of classroom teaching, experimental training, and market environment gradient. Strengthen the integration of production and education, the institutional mechanism of school-enterprise cooperation, and simplify the evaluation of learning outcomes. Develop application talents with the ability to "innovate, creative and entrepreneurial".